2010
DOI: 10.1089/fpd.2009.0452
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Quarantine Method for Mangoes Against the Mexican Fruit Fly Based on High-Pressure Processing Combined with Heat

Abstract: The Mexican fruit fly Anastrepha ludens Loew (Diptera: Tephritidae) is one of the most important insects infesting mangoes, citrus, and other fruits in Mexico and other Latin-American countries. Quarantine methods approved to destroy this insect decrease the shelf life of commodities. The objective of this study was to determine the effect of high-pressure processing using an initial temperature of 50 degrees C on the survivorship of eggs and larvae of the Mexican fruit fly. Eggs and larvae were pressurized at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The temperature and pressure levels of the treatments were selected on the basis of previous studies that have shown that 508C is needed (Velazquez et al, 2009b) and mangoes are not resistant to HPP above 100 MPa (Candelario-Rodríguez et al, 2009). HPP needs short process time to be profitable (Velazquez et al, 2005a(Velazquez et al, , 2005b.…”
Section: High Hydrostatic Pressure Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…The temperature and pressure levels of the treatments were selected on the basis of previous studies that have shown that 508C is needed (Velazquez et al, 2009b) and mangoes are not resistant to HPP above 100 MPa (Candelario-Rodríguez et al, 2009). HPP needs short process time to be profitable (Velazquez et al, 2005a(Velazquez et al, , 2005b.…”
Section: High Hydrostatic Pressure Systemmentioning
confidence: 99%
“…Recently, it was shown that A. ludens larvae were able to resist and pupate even after being pressurized at 150 MPa for 20 min at 258C (Candelario-Rodríguez et al, 2009), 150 MPa for 10 min at 08C (Velazquez et al, 2009a), and at 75 MPa for 0 min at 508C (Velazquez et al, 2009b).…”
Section: Formation Of Pupae From Surviving Larvaementioning
confidence: 99%
See 3 more Smart Citations